Bipolar disorder in a national survey using the World Mental Health Version of the Composite International Diagnostic Interview: the impact of differing diagnostic algorithms. (20th August 2012) - Mitchell, P. B.; Johnston, A. K.; Frankland, A.; Slade, T.; Green, M. J.; Roberts, G.; Wright, A.; Corry, J.; Hadzi‐Pavlovic, D.
<x xml:space="preserve">Abstract</x> Mitchell PB, Johnston AK, Frankland A, Slade T, Green MJ, Roberts G, Wright A, Corry J, Hadzi‐Pavlovic D. Bipolar disorder in a national survey using the World Mental Health Version of the Composite International Diagnostic Interview: the impact of differing diagnostic algorithms. Objective: The World Mental Health Version of the Composite International Diagnostic Interview (WMH‐CIDI) DSM‐IV bipolar disorder diagnostic algorithms were recalibrated in about 2006 following evidence of over‐diagnosis of bipolar I disorder. There have been no reports of the impact of this recalibration on epidemiological findings. Method: Data were taken from the 2007 Australian National Survey of Mental Health and Wellbeing. Findings for cases identified by the recalibrated bipolar disorder definition were contrasted against those identified by the un‐recalibrated definition. Results: The 12‐month prevalence of recalibrated bipolar disorder and un‐recalibrated bipolar disorder were 0.9% and 1.7% respectively. The un‐recalibrated bipolar disorder group was younger and more likely to have never married than the recalibrated bipolar disorder group. They were also more likely to have a comorbid alcohol use disorder, substance use disorder and asthma or arthritis. While they were more likely to have at least severe interference in at least one of the Sheehan Scale domains of functioning, they were less likely to have made a suicide attempt. Similarly, they were less likely to have consulted a psychiatrist. Conclusion: It is not possible to be certain about the nature of these differences. Some may be artifactual (reflecting greater statistical power to detect differences with the larger un‐recalibrated bipolar disorder defined sample), while others may be indicative of the inclusion of a clinically distinct subpopulation with the un‐recalibrated bipolar disorder definition, thereby producing a more heterogeneous sample. These findings indicate the need for clarity in the diagnostic algorithm used in epidemiological reports on bipolar disorder using the World Mental Health Version of the Composite International Diagnostic Interview.